2002
DOI: 10.1038/sj.bmt.1703675
|View full text |Cite
|
Sign up to set email alerts
|

Histological improvement with lamivudine therapy for de novo hepatitis B occurring in an anti-HBs-positive child after bone marrow transplantation

Abstract: Summary:We describe a 14-year-old bone marrow transplant recipient who was anti-HBs-positive before the procedure and afterwards developed acute infection with hepatitis B virus (HBV). Liver biopsies taken while symptomatic showed portal fibrosis progressing to cirrhosis. The patient responded to lamivudine treatment with HBeAg seroconversion and significant regression of fibrosis. Although the source and timing of HBV exposure remain unclear, the potential for severe hepatitis B infection following bone marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Few reports regarding the use of lamivudine for the treatment of HBV in children are available (13, 17, 18); these reports, including non‐immunocompromized patients, concluded that the treatment with lamivudine was associated with a significantly higher rate of virologic response (17) and a good tolerability. Some single pediatric case reports and single center studies involving children affected by hematological malignancies have been published (3, 19). Shapira et al.…”
Section: Discussionmentioning
confidence: 99%
“…Few reports regarding the use of lamivudine for the treatment of HBV in children are available (13, 17, 18); these reports, including non‐immunocompromized patients, concluded that the treatment with lamivudine was associated with a significantly higher rate of virologic response (17) and a good tolerability. Some single pediatric case reports and single center studies involving children affected by hematological malignancies have been published (3, 19). Shapira et al.…”
Section: Discussionmentioning
confidence: 99%
“…Reversal of severe hepatic fibrosis can occur with eradication of chronic hepatotropic viral infection (5). Our experience with chronic hepatitis B showed that achieving maximal control of the hepatitis B infection led to resolution of hepatic fibrosis (6). Cirrhosis or even severe fibrosis is infrequent in childhood chronic hepatitis C (7), but this patient had extensive fibrosis.…”
Section: Discussionmentioning
confidence: 99%